Infrared Characterisation of Zirconium(IV) Soaps. - VARMA , R.P.; SINGHAL., G.K. (Asian Journal of Chemistry, 2010)
Zirconium(IV} soaps (C6 to C16) were prepared by metathesis and their characteristics in the solid state were studied by the infrared technique to obtain the structural information.